Analyzing Critical Thinking and Mathematical Communication Skills of Junior High School Students Based on Intrapersonal and Interpersonal Intelligence (International Journal of Scientific Research and Management (IJSRM), 2025)
This research aims to describe the profile of students’ critical thinking abilities, mathematical communication abilities, and intrapersonal and interpersonal intelligence, as well as analyze their influence on critical thinking and mathematical communication abilities. A survey was conducted on 368 eighth-grade junior high school students in Yogyakarta City, selected using a proportionate stratified random sampling technique based on Regional Education Standardization Assessment (ASPD) scores. The instruments used included intrapersonal and interpersonal intelligence questionnaires, as well as tests for mathematical communication and critical thinking skills. Data were analyzed using descriptive and inferential statistics, with a focus on multiple linear regression analysis. The results show that the average students’ critical thinking and mathematical communication skills are moderate, with percentages of 53.2% and 51.9%, respectively. Similarly, the average intrapersonal and interpersonal intelligence of eighth-grade students in Yogyakarta is moderate, with a percentage of 48.3%. Students with high intrapersonal and interpersonal intelligence tend to demonstrate high critical thinking and mathematical communication skills, with respective percentages of 53% and 61%. Furthermore, intrapersonal and interpersonal intelligence significantly affect mathematical communication skills but do not have a significant effect on critical thinking skills.